Effects of saxagliptin add-on therapy to insulin on blood glycemic fluctuations in patients with type 2 diabetes: A randomized, control, open-labeled trial. Issue 43 (October 2016) - Li, Feng-fei; Jiang, Lan-lan; Yan, Reng-na; Zhu, Hong-hong; Zhou, Pei-hua; Zhang, Dan-feng; Su, Xiao-fei; Wu, Jin-dan; Ye, Lei; Ma, Jian-hua
Abstract: Background: To investigate whether saxagliptin add-on therapy to continuous subcutaneous insulin infusion (CSII) further improve blood glycemic control than CSII therapy in patients with newly diagnosed type 2 diabetes (T2D). Methods: This was a single-center, randomized, control, open-labeled trial. Newly diagnosed T2D patients were recruited between February 2014 and December 2015. Subjects were divided into saxagliptin add-on therapy to CSII group (n = 31) and CSII therapy group (n = 38). The treatment was maintained for 4 weeks. Oral glucose tolerance test was performed at baseline. Serum samples were obtained before and 30 and 120 minutes after oral administration for glucose, insulin, and C-peptide determination. Continuous glucose monitoring (CGM) was performed before and endpoint. Results: A total of 69 subjects were admitted. After 4-week therapy, CGM data showed that patients with saxagliptin add-on therapy exhibited further improvement of mean amplitude glycemic excursion (MAGE), the incremental area under curve of plasma glucose >7.8 and 10 mmol/L compared with that of control group. In addition, the hourly mean blood glucose concentrations, especially between 0000 and 0600 in patient with saxagliptin add-on therapy, were significantly lower compared with that of the control patients. Furthermore, patients in saxagliptin add-on group needed lower insulin dose to maintain euglycemic control. In addition, severe hypoglycemic episode was not observed from any group. Conclusion: Saxagliptin add-on therapy to insulin had the ability of further improve blood glycemic controlling, with lower insulin dose required by patients with T2D to maintain euglycemic controlling.